Multiple-layer energy management strategy for charging station optimal operation considering peak and valley shaving - Qian, Bin; Song, Min; Ke, Song; Zhang, Fan; Luo, Bin; Wang, Ji; Tang, Jianlin; Yang, Jun (Frontiers in Energy Research, 2023)
Existing vehicle-to-grid (V2G) applications are aimed at the power grid and the government. It is difficult for charging stations (CSs) to execute the schedules in real time. The multiple-layer energy management from the perspective of the charging station (CS) needs to be figured out. First, the dispatch potential assessment model is constructed based on the EV users' charging demand and Minkowski summation. Next, the optimal energy management schedule model of CS with ESS is proposed considering the peak shaving and valley filling under the time-in-use tariff. Third, the realtime charging control model of EVs in the CS is designed under the premise of meeting the charging needs. The simulation results show that the proposed strategy can promote the CS operation revenues and the scheduling plan of the CS can be tracked. The arbitrage of tariffs and peak shaving ancillary services are realized while the charging loads of CSs are smoothed by the charging/discharging of the ESS.